Development of a novel DNA-launched dengue virus type 2 infectious clone assembled in a bacterial artificial chromosome (2014)
ABSTRACT: Major progress in Dengue virus (DENV) biology has resulted from the use of infectious clones obtained through reverse genetics. The construction of these clones is commonly based on high- or low-copy number plasmids, yeast artificial chromosomes, yeast-Escherichia coli shuttle vectors, and bacterial artificial chromosomes (BACs). Prokaryotic promoters have consistently been used for the transcription of these clones. The goal of this study was to develop a novel DENV infectious clone in a BAC under the control of the cytomegalovirus immediate-early promoter and to generate a virus with the fusion envelope-green fluorescent protein in an attempt to track virus infection. The transfection of Vero cells with a plasmid encoding the DENV infectious clone facilitated the recovery of infectious particles that increased in titer after serial passages in C6/36 cells. The plaque size and syncytia phenotypes of the recombinant virus were similar to those of the parental virus. Despite the observation of autonomous replication and the detection of low levels of viral genome after two passages, the insertion of green fluorescent protein and Renilla luciferase reporter genes negatively impacted virus rescue. To the best of our knowledge, this is the first study using a DENV infectious clone under the control of the cytomegalovirus promoter to facilitate the recovery of recombinant viruses without the need for in vitro transcription. This novel molecular clone will be useful for establishing the molecular basis of replication, assembly, and pathogenesis, evaluating potential antiviral drugs, and the development of vaccine candidates for attenuated recombinant viruses.